استكشاف دور تكنولوجيا البلوكتشين في تعزيز تكامل سلسلة التوريد والتعاون بينها - طارق عبدالعزيز بشير الصواني; ايمان بلقاسم صغير رحال; نسرين عبدالعزيز بشير الصواني (Surman Journal of Science and Technology, 2025)
Despite some debates surrounding blockchain technology, it has been highlighted as a significant distributed and secure technology of the 21st century. It is a tamper-proof digital ledger for economic transactions that can be programmed to record not only financial transactions but almost anything of value. Blockchain is a revolutionary technology that will transform industries internationally, adding value to companies and supply chain networks, enhancing trade, and boosting the economy. Although blockchain has garnered attention, very few studies have focused on supply chain integration and collaboration areas. This study demonstrates the potential of applying blockchain technology to coordinate activities for effective and efficient supply chain management. The study focuses on the use of blockchain in supply chains beyond cryptocurrencies, payments, and finance by employing smart contracts and consensus algorithms (i.e., enforcing constraints). The key features of blockchain are discussed, and potential questions in Libya are identified. The expected outcome of this study will enhance the understanding of blockchain and supply chain literature, while also inspiring researchers and practitioners to consider blockchain applications in future studies that take different contexts into account.